Pengaruh PENGARUH CURRENT RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON INVESMENT PADA PERUSAHAAN SEKTOR KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2017- 2019 - Wulan Ayuandiani S.E., M.M (Jurnal Pasar Modal dan Bisnis, 2021)
The purpose of this study was to determine the effect of the Current Ratio and Total Asset Turnover on Return On Invesment through statistical analisis methods during the 2017-2019 period. This research was conducted in construction sector companies listed on the Indonesian Stock Exchange. This research used is a quantitatif descriptive method and the secondary data. Secondary data in from of financial statement of construction sector companies for 2017-2019 period. The type of data used is quantitative data with documentation collection techniques. Based on the result of the t-test research, it can be concluded that the Current Ratio have not significant effect on Return On Investment of construction sector companies 2017-2019 period. Based on the result of the t-test research, it can be concluded that the Total Asset Turnover of construction sector companies have positive and significant effect on Return On Investment of construction sector companies 2017-2019 period. Based on the F test simultaneously both of Current Ratio and Total Asset Turnover have positive and significant effect on Return On Investment of construction sector companies 2017-2019 period.